2017
DOI: 10.17221/398/2016-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous yeasts perform alcoholic fermentation and produce aroma compounds in wine

Abstract: AbstractČuš F., Zabukovec P., Schroers H.J. (2017): Indigenous yeasts perform alcoholic fermentation and produce aroma compounds in wine. Czech J. Food Sci., 35: 329-345.The spontaneous alcoholic fermentations of Moscato Bianco and Welschriesling must were carried out to retrieve indigenous yeasts. We confirmed that those fermentations, conducted with non-Saccharomyces and indigenous Saccharomyces cerevisiae yeasts, can generate high amounts of aroma compounds in wines. Consequently, two of the S. cerevisiae i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
2
3
0
Order By: Relevance
“…The presence of varietal thiols in Welschriesling wines was also reported by (Čuš and Zabukovec, 2017;Maslov Bandić et al, 2018). The observed concentration range for varietal thiols was similar to that in our study (Čuš and Zabukovec, 2017).…”
Section: Commercial Welschriesling Wine Volatile Profilesupporting
confidence: 71%
See 1 more Smart Citation
“…The presence of varietal thiols in Welschriesling wines was also reported by (Čuš and Zabukovec, 2017;Maslov Bandić et al, 2018). The observed concentration range for varietal thiols was similar to that in our study (Čuš and Zabukovec, 2017).…”
Section: Commercial Welschriesling Wine Volatile Profilesupporting
confidence: 71%
“…The presence of varietal thiols in Welschriesling wines was also reported by (Čuš and Zabukovec, 2017;Maslov Bandić et al, 2018). The observed concentration range for varietal thiols was similar to that in our study (Čuš and Zabukovec, 2017). However, the 3MH and 3MHA concentrations measured in Chardonnay wines (Capone et al, 2018) and our study were still below observed concentrations in commercial Sauvignon blanc wines from New Zealand, South Africa or France (Lund et al, 2009).…”
Section: Commercial Welschriesling Wine Volatile Profilesupporting
confidence: 71%
“…cis-Rose oxide, linalool, and geraniol had also been reported in odor-active amounts, that is in concentrations exceeding their OTCs, in Muskateller grapes and wines. 8,9,25,26 Given the gaps in the literature detailed above, our aims were to characterize the major odor-active compounds in Muscaris grapes, compare them with the odor-active compounds in the grapes of its father variety, Muskateller, and elucidate the molecular background of the lychee note in the aroma of the Muscaris grapes. This knowledge is a prerequisite for further research, e.g., on odorant transfer from Muscaris grapes into wine and for targeted breeding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Among them, cis -rose oxide, β-damascenone, ethyl 2-methylpropanoate, linalool, and geraniol consistently showed concentrations beyond their odor threshold concentrations (OTCs). cis -Rose oxide, linalool, and geraniol had also been reported in odor-active amounts, that is in concentrations exceeding their OTCs, in Muskateller grapes and wines. ,,, …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation